Flooded Lead Acid Battery SOC Estimation for Energy Conscious LVDC Building: Warm and Humid Climate - Chacko, Rani; Thevarkunnel, Adarsh; Varghese, Lakaparampil Zachariah; Thomas, Jaimol (Trends in Sciences, 2022)
Microgrids make it easier to integrate Renewable Energy Sources (RESs) and Energy-Storage Systems (ESSs) at the consumer level, with the intent of enhancing power quality, reliability, and efficiency. This microgrid concept at the nano grid level is championed by a low voltage DC (LVDC) grid, facilitating the direct integration of several distributed generators, storage and loads that are almost DC source/load. Since the State of Charge (SOC) of the battery is an essential parameter for building energy management systems, careful monitoring of SOC is essential. The SOC of a battery directly reflects its performance; thus, straightforward, reasonably accurate, and timely estimation of SOC protects against overcharging or discharging issues, with fewer processor requirements and computations. A novel SOC estimation method is proposed based on the literature assessment of different existing SOC estimation methods. In regions with a tropical climate, the temperature range over the year is small, and the sunshine is relatively intense and fairly even throughout the year. Also, for all practical purposes, it is a fact that the model that takes inputs at the point of use gives accurate results. Considering the 2 facts mentioned above, the current model uses a less complicated algorithm, within acceptable accuracy for the purpose and relatively user-friendly. HIGHLIGHTS State Of Charge (SOC) estimation of 48V Lead Acid battery for Low Voltage DC (LVDC) building energy management systems Straightforward, reasonably accurate, and timely estimation of SOC which protects against overcharging or discharging issues, with fewer processor requirements and computations For the SOC estimation, the open-circuit voltage is obtained by measuring the terminal voltage, current and first-order model of the battery developed under similar climatic condition Development and testing of an algorithm incorporating temperature-independent first-order battery model for the tropical climate with lesser temperature variation GRAPHICAL ABSTRACT